Case Report: Radiological Features of Sclerosing Epithelioid Fibrosarcoma in the Right Fibula - Ding, Qiaoling; Shao, Xiaotong; Liu, Xiaocao; Fu, Yanbiao; Huang, Fengbo; Wang, Chao (Frontiers in Oncology, 2020)
Background: Sclerosing epithelioid fibrosarcoma (SEF) is an extremely rare, aggressive malignant subtype of fibrosarcoma. Only dozens of cases of primary SEF in the bone have been reported so far, without case involving fibula reported in literature to date. Herein we report the first case of primary SEF in the right fibula in a 19-year-old man. In this case report, we firstly give a comprehensive description of fibula SEF, including its complete clinical course and radiological findings. Case Presentation: A 19-year-old man presented with a half-year history of soreness in the right lower leg. Contrast-enhanced computed tomography (CE-CT) and magnetic resonance imaging (MRI) of the right lower leg were performed. Based on the radiological examinations, a diagnosis of malignant tumor arising in the fibular diaphysis was made. Final diagnosis of primary SEF in the right fibula was confirmed by histopathological and immunohistochemical examinations after surgical resection. The patient had no signs of recurrence or metastasis during a 24-month follow-up. Conclusion: We report an exceedingly rare case of primary SEF in the right fibula and its radiological features with CE-CT and MRI.